2019
DOI: 10.3390/ijerph16061025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neighborhood Discrimination Towards Mainland Immigrants on Mental Health in Hong Kong

Abstract: Using data from a representative sample of Chinese adults who were surveyed in the Hong Kong Panel Study of Social Dynamics (HKPSSD), we estimate the effects of neighborhood discrimination towards immigrants from Mainland China on the mental health of Chinese residents in Hong Kong. Contrary to our expectations, discrimination towards immigrants from Mainland China measured at the neighborhood level is not associated with the poor mental health of post-1997 immigrants; instead, a higher level of immigrant disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Discriminatory stress is common for new immigrants (Chen et al, 2019;Di Napoli et al, 2021;Esses, 2021). According to the temporal need-threat model (K. D. Williams, 2009), being discriminated against threatens an individual's need to understand their immediate environment and control how they should behave.…”
Section: Tolerance Of Uncertainty: Individual-level Coping Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Discriminatory stress is common for new immigrants (Chen et al, 2019;Di Napoli et al, 2021;Esses, 2021). According to the temporal need-threat model (K. D. Williams, 2009), being discriminated against threatens an individual's need to understand their immediate environment and control how they should behave.…”
Section: Tolerance Of Uncertainty: Individual-level Coping Resourcesmentioning
confidence: 99%
“…Immigration is a prominent social and political issue globally (Chen et al, 2019; Di Napoli et al, 2021; Esses, 2021). Hong Kong is a unique city, with a large number of immigrants arriving from Mainland China annually.…”
Section: The Cultural and Developmental Psychopathology Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the questions captured by these measures, however, were related to participants’ daily interactions (e.g. “I don't think I am treated fairly in restaurants” or “Others don't respect me enough”); thus, it is reasonable to assume that these perceived discriminatory behaviors against them were perpetuated by local residents, as most discrimination against new immigrants mainly comes from local residents (Chen et al., 2019; Fong & Guo, 2019; Ng et al., 2015; Wong et al., 2012). In addition, children may face discrimination in different contexts (discrimination from peers and teachers) from their mothers (in the labor market or neighborhood), which may account for discrepant reports (Rivas‐Drake et al, 2008).…”
Section: Limitationsmentioning
confidence: 99%
“…Previous studies identified a positive association between perceived discrimination and various adverse outcomes among migrants (Lee & Ahn, 2011; Pascoe & Smart Richman, 2009). For example, higher levels of perceived discrimination predicted more mental health disorders such as depression and anxiety among migrant children (Chen et al, 2019) and mothers (Chang et al, 2020). Few studies, however, have addressed these detrimental linkages among migrant children and mothers by using a dyadic approach to examine how children's and their mothers’ experiences of discrimination and mental health are intertwined (Chou, 2012).…”
Section: Introductionmentioning
confidence: 99%